Dispersive solid-phase imprinting of proteins for the production of plastic antibodies. Issue 27 (15th March 2018) - Ashley, Jon; Feng, Xiaotong; Halder, Arnab; Zhou, Tongchang; Sun, Yi
Abstract : A new imprinting technique, so called dispersive solid-phase imprinting, has been developed for the production of nano-sized molecularly imprinted polymers (nanoMIPs) as plastic antibodies. Abstract : We describe a novel dispersive solid-phase imprinting technique for the production of nano-sized molecularly imprinted polymers (nanoMIPs) as plastic antibodies. The template was immobilized on in-house synthesized magnetic microspheres instead of conventional glass beads. As a result, high-affinity and template-free MIPs were produced in higher yields.